Diagnostic applications of cell-free and circulating tumor cell-associated miRNAs in cancer patients. (April 2011) - Mostert, Bianca; Sieuwerts, Anieta M; Martens, John WM; Sleijfer, Stefan
Recently, miRNA-expression profiling in primary tumors has yielded promising results. However, establishing miRNA expression in the circulation probably has advantages over determination in primary tumor tissue, further augmenting the potential applications of miRNA determination in oncology. Circulating tumor cells (CTCs) have rapidly developed as important prognostic and therapy-monitoring biomarkers in metastatic breast, colorectal and prostate cancer when enumerated, and their isolation enables subsequent analysis using various molecular applications, including miRNA-expression analysis. In addition to CTC-associated miRNAs, free circulating miRNAs have been identified in whole blood, plasma and serum. Determination of miRNAs in peripheral blood, either cell-free or CTC-associated, is expected to become important in oncology, especially when linked to and interpreted together with epithelial CTCs. In this article, we will discuss miRNA-expression profiling in primary tumors, depict the potential applications of measuring miRNA in the circulation and review the literature on cell-free circulating miRNAs, as well as offering some methodological and technical considerations on the measurement of circulating miRNAs.